Opportunities Abound : Public Private Partnerships for Laboratory Services in East Africa - Ravishankar, Nirmala; Lehmann, Joel (World Bank, Washington, DC, 2015)
This document presents findings from a study conducted to identify and document ongoing public-private partnerships (PPPs) for improving access to quality laboratory services, especially for the poor, in the East Africa region. The East, Central, and Southern Africa Health Community (ECSA-HC) coordinated the study along with the partner states in the East African Community participating in the World Bank funded East Africa Public Health Laboratory Networking Project (EAPHLNP). The authors implemented key informant interviews in Kenya, Rwanda, Tanzania and Uganda, and analyzed the information gathered from the interviews which is presented in this report. The study finds that while there are numerous examples of public-private collaboration across all four countries, the number of formals PPPs remains scarce. The most common form of PPP is placement, whereby privately owned laboratory equipment in leased by public facilities. Most other instances of collaboration between public and private partners, did not meet the formal definition of a PPP. Key stakeholders from both public and private institutions showed a keen interest in learning about and setting up more, diverse kinds of PPPs. The numerous informal and semi-formal arrangements that currently exist all represent opportunities for establishing formal PPPs in accordance with global best practices.